Challenging for some, utopian for others: the poor regulation of training practices and its negative impact on people with disabilities - Verano Calero, Magda Cristina (2020)
In recent years higher education has undergone major changes. However, the poor regulation of training practices has remained. The purpose of this article is to analyze the regulation of training practices, and their lack of recognition as work under the current legal framework, a situation that disproportionately affects students with disabilities. Finally, a brief account is given of the main findings of interviews with law students with disabilities in this field.